2020
DOI: 10.18203/2319-2003.ijbcp20200192
|View full text |Cite
|
Sign up to set email alerts
|

Syzygium cumini (jamun) therapeutic potential: a comprehensive review on phytochemical constituents and emphasis on its pharmacological actions related to diabetic intervention

Abstract: Syzygium cumini or Eugenia Jambolana Lam is a traditional medicinal plant very native to the Indian and Asian sub-continent. It is commonly known as black plum or jamun. Various plants parts of the tree are known for ethno-medicinal uses, and in particular, the fruits of Jamun tree are well known for medicinal uses and preparation of health drinks. Studies have shown that the berries contain carbohydrates, minerals and the pharmacologically active phytochemicals. The active phytochemical includes flavonoids, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Jamun seeds are mentioned in the ayurvedic pharmacopoeia as a medication for diabetes. Taking this lead from Ayurveda, extracts of different parts of this plant have been tested for antidiabetic activities and among these the seeds have shown more promise (6).…”
Section: Introductionmentioning
confidence: 99%
“…Jamun seeds are mentioned in the ayurvedic pharmacopoeia as a medication for diabetes. Taking this lead from Ayurveda, extracts of different parts of this plant have been tested for antidiabetic activities and among these the seeds have shown more promise (6).…”
Section: Introductionmentioning
confidence: 99%
“…Ayurvedic and Indian Folk Medicine have elaborated the use of this plant for diabetic treatment before the advent of insulin. 5 Based on the biochemical screening of methanolic and aqueous leaves extracts of Syzygium cumini, it showed that those extracts contained alkaloids, saponins, carbohydrates, flavonoids, terpenoids, glycosides and proteins. 6 Moreover, four types of flavonoid compounds are present in leaf extract of Syzygium cumini, quercetin, rutin, ellagic acid and kaempferol.…”
mentioning
confidence: 99%